ANALISIS PENGENDALIAN KUALITAS MENGGUNAKAN DIAGRAM KENDALI DEMERIT (Studi Kasus Produksi Air Minum Dalam Kemasan 240 ml di PT TIW) - Gita Suci Ramadhani; Yuciana Wilandari; Suparti Suparti (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
The efforts to maintain and improve the quality of the resulting product with statistical process control. Demerit control chart is a control chart in which the defect type is categorized into several classes according to the level of disability interests. Types of defects in the production processes of bottled water 240 ml in PT TIW divided into critical defects, major defects and minor defects. Based on the results of the analysis that has been done shows that the production process has been controlled statistically using demerit control charts on the third iteration for each line 1 and line 2. Capability of production processes in line 1 and line 2 shows that although the production process has been controlled statistics, but the process still produces a product that is not in accordance with specifications. But in the end all defective products are produced, will be immediately discarded and will not be marketed or sold to the consumer. This is done for the commitment PT TIW who always maintain the best quality products. Based on pareto chart for this type of defect on line 1 and line 2, it is known that 20% of the total types of defects, obtained two types of defects which constitute 80% of disability of the entire production process. The defect type is slanted lid and reject filler. The factors that cause this type of defect are slanted lid and reject filler among others, there is a worn machine components and uncorrect machine settings, the operator has not been retrained and lack of focus so not accordance with the procedure in the work, the composition of the materials is uncorrect, and methods or procedures are less well executed.